Effect of land use differences on pH and available Phospor in Peatland, Kelampangan, Central Kalimantan - Fitri Wijayanti; Haidar Fari Aditya; Adi Jaya; Winih Sekaringtyas Ramadhani; Raudah Anggraini Tarigan (Nusantara Science and Technology Proceedings, 2022)
This extraordinary peatland area can have various impacts, especially in Indonesia and even globally. In general, in soil classification, peat soil is known as Histosol. Based on the maturity level, there are safric, fabric, and hemic maturity levels. In general, peat soils have a relatively high level of acidity with a pH range of 3-4. Peatland management in the Central Kalimantan region has developed quite rapidly where many peatlands can be used as agricultural lands, such as in the Kalampangan area. Several types of land use analyzed in this study are dragon fruit monoculture, agroforestry with chili as the main crop, burnt forest, and natural peat forest. The analysis was carried out to determine the pH and available P content in the peat soil on each land use. The pH range in each land use is acidic with the highest actual pH range of 4 in the dragon fruit monoculture land use and the lowest in the natural forest landuse of 3,2. Meanwhile, the potential pH has a fairly similar value in the range of 2.1 to 2.5. The highest available P was obtained in chili agroforestry and the lowest was in the burnt forest. The highest available P was obtained in chili agroforestry and the lowest was in the burnt forest. The available pH and p values are strongly influenced by the management carried out by farmers, whereas in some areas the management is carried out quite intensively. An inventory of peat characteristics data is needed for current and future land development.